Glarborg – en glashytte fra renæssancen i Gribskov, Nordsjælland - Appel, Liv; Jouttijärvi, Arne (Hikuin, 2010)
Glarborg – a Renaissance glassworks from the forest of Gribskov, Northern Zealand By Liv Appel and Arne Jouttijärvi Archaeo-metrical analysis of finds originating from archaeological investigations carried out by Gilleleje Museum at Glarborg in the Gribskov forest from 2003-2006 show, that both slags, parts of ovens, glass pots and shards of glass all stem from a Renaissance glassworks. The precise position of the glasseworks itself has not yet been established, however as cultivation in the forest area had ceassed already by the end of the 18th century, the glassworks site could well be preserved undisturbed and thus be a viable object for further research investigations. The first part of the placename Glarborg stems from the Old Danish word glar, meaning glass, whilst the last part borg refers to an older fortified site nearby. When the name Glarborg first crops up in the written sources in 1555, the site was most probably younger than the other settlement sites in the forest founded in the 11th -12th century. The Danish King Christian III (1534-1559) undoubtedly required a supply of glass for his royal castles in Elsinore and Cophenhagen and the citing of a glassworks in the Gribskov forest would have been an obvious choice, as it had been a crown posscession from the beginning of the medieval period. By all accounts it seems, that the glassworks was located in a natural forest clearing created by a storm, with ample supplies of wood for firing charcoal to heat the glassovens. Archaeo-metrical analysis shows, that the glassmaker and his workers had been brought in from Hessen. The glassmaker possibly received the tenancy of the farm, that was created by forest clearence before 1555 and which took the name of the glassworks. Both the archaeological and the written sources indicate, that there was an unusal level of affluence at Glarborg right up until the end of the 17th century. It’s possible, that the tenant farmer managed to earn enough money and was shown soo much good will by both the kings officers and the King himself – in the short time that glass was produced at Glarborg – that he sucessfully built up the farms animal flocks, which consequently ensured the farms affluence right through the 17th century.